If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 7n = 9n Solving 4 + 7n = 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. 4 + 7n + -9n = 9n + -9n Combine like terms: 7n + -9n = -2n 4 + -2n = 9n + -9n Combine like terms: 9n + -9n = 0 4 + -2n = 0 Add '-4' to each side of the equation. 4 + -4 + -2n = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -2n = 0 + -4 -2n = 0 + -4 Combine like terms: 0 + -4 = -4 -2n = -4 Divide each side by '-2'. n = 2 Simplifying n = 2
| 8(8a+8)=-64 | | 3[2-(2t+5)]-1=2(5-t) | | 42=-4k | | 6·1-6/1 | | -7(n-4)=-28 | | 3b-3b+b-b+b=9 | | 14w-5w+5=14 | | 6x+18=10+8x | | 0.25x+5=5+0.25x | | 15tan^3x=5tanx | | 28.00+.2x=40 | | 25y-10= | | 3(k+2)=-12 | | 5x+8-4x=0 | | 6+2(z+3)=-4(2z+6) | | 2y-3+3(3y+4)=-3(y+1) | | 1=3-c | | 2m+6=-10 | | 10/10-10/1 | | 10t+t+t-t-t=10 | | (4(y-6))/3=-2y | | -4(-m-5)-7=-11 | | 0=4p-28 | | x+10=x+90 | | 1/2x+5=1/2x-3 | | 5(p-6)=8p-21 | | -(9m+10)+2= | | 8u-8u+u-1=5 | | 12+2n=5n | | 7-5(x+8)=43 | | 8c+2b= | | 4(k+6)=56 |